POLA KOMUNIKASI INTERPERSONAL GURU DAN MURID DALAM PEMBELAJARAN DARING (Studi Fenomenologi Pada Guru dan Murid SD Negeri 03 Bukit Duri Jakarta) - Nur Syifa Maulidah (2022)
With the pandemic, there have been changes in learning, especially in elementary schools. This study aims to determine the pattern of interpersonal communication between teachers and students in online learning at SD Negeri 03 Bukit Duri Jakarta and to determine the factors supporting and inhibiting the occurrence of interpersonal communication patterns between teachers and students in online learning at SD Negeri 03 Bukit Duri Jakarta. This research uses symbolic interaction theory. The method used is descriptive qualitative. The results of this study indicate that the one-way communication pattern is still applied by teachers and students in online learning due to the limited space and scope of learning. In addition, two-way communication patterns still play an important role so that communication runs well and effectively. Supporting factors in the pattern of interpersonal communication between teachers and students, namely students are not passive when learning, parents participate in collaboration when learning online, cellphones and laptops do not have problems, there is openness between teachers and students in interacting, and high self-awareness of students and teachers when implementation of distance learning. The inhibiting factors for the pattern of interpersonal communication between teachers and students are internet network errors, student gadgets used by people at home together and parents who do not accompany their children to study online. Keywords: Learning, Online, Students, Teachers.